Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn) protein-derived antioxidant peptides: mechanisms of action and structure-activity relationship in Caco-2 cell models - Yiming Zhou; Xuanming She; Zhidong Chen; Yun Wei; Ying Xiao; Xiaoli Zhou (Food Science and Human Wellness)
Excessive reactive oxygen species (ROS) can cause oxidative damage and lead to various metabolic disease. Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn) is a new kind of protein-rich functional food, the protein in which has been proved to have good antioxidant capacity. In this study, in order to further explore the antioxidant mechanism of Tartary buckwheat protein, 4 peptides (CR-8, LR-8, GK-10 and SR-12) were isolated and identified from it. H2O2 was used to induce oxidative damage to Caco-2 cells to evaluate antioxidant capacity of these peptides. The results of superoxide dismutase (SOD), total antioxidant capacity (T-AOC) and mitochondrial membrane potential etc. showed that these peptides have superior antioxidant capacity. CR-8 has the best antioxidant capacity. In order to further clarify the antioxidant mechanism of CR-8, metabolomics was used to analyze related metabolites and metabolic pathways. The results showed that after CR-8 intervention, the content of metabolites such as L-acetyl carnitine has increased. This indicated that CR-8 can improve the antioxidant capacity of damaged cells by intervening in multiple metabolic pathways. This also revealed the anti-oxidant mechanism of tartary buckwheat protein. In conclusion, it provided a theoretical basis for further studying the activity of tartary buckwheat portein and utilizing buckwheat resources.